Relationship between MRI features and HIF-1α, GLUT1 and Ki-67 expression in pituitary adenoma with cystic degeneration - Fangfang Zhang; Zhenhong Pan; Jianwu Wu; Yinxing Huang (BMC Medical Imaging, 2025)
Abstract Background Pituitary adenomas (PAs) are prevalent tumors that often exhibit ischemia, hypoxia, and cystic transformations, impacting their prognosis. The relationship between cystic degeneration in PAs and the expressions of hypoxia-inducible factor-1α (HIF-1α), glucose transporter 1 (GLUT1), and Ki-67 remains unclear. This study aims to analyze the correlation between MRI characteristics of cystic PA and the expression of these proteins. Methods This is a retrospective analysis. A total of 74 patients with cystic PA and 30 PA patients without cystic degeneration were enrolled. Their MRI signs were analyzed. According to the T2WI signs of PA, they were divided into the fluid level group (n = 26), non-fluid level group (n = 48), and non-cyst group (n = 30). Immunohistochemistry was performed to evaluate the expression levels of HIF-lα, GLUT1, and Ki-67 protein. Univariate and multinomial logistic regression analyses were used to evaluate the factors affecting MRI signs of PA. Spearman correlation was also performed. Results There was no significant difference in gender, age, and HIF-1α protein expression among the three groups. Significant differences were found in invasiveness (P = 0.008), GLUT1 (P < 0.001), and Ki-67 protein expression (P = 0.009) among the three groups. Pairwise comparisons revealed statistically significant differences in invasiveness, GLUT1, and Ki-67 protein expressions between the non-fluid level group and the non-cyst group. Furthermore, GLUT1 protein expression was significantly different between the non-fluid level group and the fluid level group. Notably, GLUT1 was identified as an independent factor for the non-fluid level cystic characteristics of PA. Additionally, GLUT1 was positively correlated with invasiveness and Ki-67. Conclusion The non-fluid level cystic PA has higher invasiveness and higher proliferation than fluid level cystic PA and non-cyst PA, which may be related to high glucose metabolism as indicated by GLUT1 expression.